Eksplorasi Implementasi Nilai-Nilai Islam dalam Praktik Ekonomi Berkelanjutan pada Peternakan Ikan Lele BUMDes Naga Rantai - Harlin Muhamat Wahyu; Herlina Yustati; Esti Alfiah (CV Global Research Publication, 2026)
This study aims to explore the application of Islamic values in the operations of BUMDes Naga Rantai's catfish farming and their contribution to village economic sustainability. Utilizing a descriptive qualitative method with a case study approach, data were gathered through in-depth interviews, direct observations, and documentation from BUMDes management, workers, and village officials, then analyzed using triangulation techniques. The results indicate that the integration of four key indicators—Tawhid, Khalifah (Amanah), Prohibition of Riba/Gharar, and Justice—has been successfully implemented within the business unit. Tawhid and Khalifah are manifested through ecological responsibility, including feed efficiency and waste management using decomposer bacteria within a circular economy model. Meanwhile, the prohibition of riba/gharar and justice are applied through transparent transaction systems, accurate product weighing, and fair wages for local workers. The internalization of these values contributes significantly as moral guidelines and operational SOPs, effectively mitigating environmental risks and business fraud while sustainably reinforcing village economic independence.